A Clear, Strong, and Thermally Insulated Transparent Wood for Energy Efficient Windows. (18th November 2019) - Mi, Ruiyu; Li, Tian; Dalgo, Daniel; Chen, Chaoji; Kuang, Yudi; He, Shuaiming; Zhao, Xinpeng; Xie, Weiqi; Gan, Wentao; Zhu, Junyong; Srebric, Jelena; Yang, Ronggui; et al.
Abstract: The energy used for regulating building temperatures accounts for 14% of the primary energy consumed in the U.S. One‐quarter of this energy is leaked through inefficient glass windows in cold weather. The development of transparent composites could potentially provide affordable window materials with enhanced energy efficiency. Transparent wood as a promising material has presented desirable performances in thermal and light management. In this work, the performance of transparent wood is optimized toward an energy efficient window material that possesses the following attributes: 1) high optical transmittance (≈91%), comparable to that of glass; 2) high clarity with low haze (≈15%); 3) high toughness (3.03 MJ m −3 ) that is 3 orders of magnitude higher than standard glass (0.003 MJ m −3 ); 4) low thermal conductivity (0.19 W m −1 K −1 ) that is more than 5 times lower than that of glass. Additionally, the transparent wood is a sustainable material, with low carbon emissions and scaling capabilities due to its compatibility with industry‐adopted rotary cutting methods. The scalable, high clarity, transparent wood demonstrated in current work can potentially be employed as energy efficient and sustainable windows for significant environmental and economic benefits. Abstract : The demonstrated transparent wood exhibits a desirable combination of high clarity, high mechanical performance, as well as low thermal conductivity. The polyvinyl alcohol acts as the infiltration polymer, which renders the transparent wood biodegradable. With a scalable fabrication method, the transparent wood can potentially be used towards energy efficient windows.